Pengaruh Carbon Monoxide (CO) dan Nitrogen Dioxide (NO2) terhadap Perubahan Land Surface Temperature (LST) di Kota Padang dengan Menggunakan Data Penginderaan Jauh - Lovani, Dion; Prarikeslan, Widya (MASALIQ, 2024)
The purpose of this study is to identify changes in the surface temperature of Land Lurface Temperature (LST) in Padang City in 2018 and 2023 and analyze the influence of Carbon Monoxide (CO) and Nitrogen Dioxide (NO2) air pollution in Padang City in 2018 and 2023. The data used in this study are Landsat OLI 8 satellite imagery and Sentinel 5P satellite image data analyzed using Geographic Information System technology. The results show that in 2018 the highest temperature reached 33°C and in 2023 the highest temperature was 28°C, then the effect of CO on LST in 2018 was significantly related to the value of the determination coefficient of (R2 = 64,9 ), and the influence of NO2 was weakly related to the value (R2 = 16,3). In 2023, the effect of CO on LST is weakly related to the value (R2 = 2) and NO2 on LST is also weakly related (R2 = 5,1). The results showed that there was a trend of changes in LST and its relationship to air pollution but showed a not very strong relationship.